Potentials of Betel Leaf Infusion (Piper betle L), Lime Peel Extract (Citrus aurantifolia) and Bundung Extract (Actinoscirpus grossus) as Candidiasis Therapy - Darini Kurniawati; Kunti Nastiti (Berkala Kedokteran, 2020)
Abstract: Candidiasis is an infection caused by the fungus Candida, especially Candida albicans. It often occurs in the mouth and sex organs, also in the nails, respiratory tract, digestive tract, and anus. Betel leaf stew is often used by people to gargle and clean the intimate organs. The nature of the betel leaf solution is easily oxidized and turns brown. Therefore, research needs to be done by mixing betel leaf (Piper betle L) with lime (Citrus aurantifolia) to maintain the color of betel leaf, coupled with natural ingredients that have antimicrobial properties, namely lime peel and bundung plants (Actinoscirpus grossus). With the hypothesis of the joining of three natural materials that have antimicrobial activity can strengthen the inhibitory activity of the fungus Candida albicans. This research was conducted by making a betel leaf infusion formulation, lime peel extract, and bundung extract with a concentration of 20%, 30%, 40%, and 50% which were then tested to determine the effect of the infusion formulation on the inhibitory activity of Candida albicans by the method spread on Saburoud Dextrose Agar media. Based on Zuraidah's research (2015), 80% and 100% betel leaf extraction has activity on Candida albicans. From the results of this study significant results were obtained at a concentration of 50% of a mixture of betel leaf infusion formulations, extracts of lime peel and bundung extract had the same inhibitory properties as the hand sanitizer antiseptic liquid against Candida albicans. Thus it can be concluded that the 50% test formulation of betel leaf infusion mixture with lime extract and bundung extract has greater potential than betel leaf extract alone as a candidiasis therapy. Keywords: Piper betle L, Citruss aurantifolia, Actinoscirpus grossus, Antiseptik, Kandidiasis, Candida albicans